The Future of Health Expenditure in ASEAN Countries: A Forecasting Analysis with ARIMA - Melati, Alexsandra Putri Sekar; Sihaloho, Estro Dariatno (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: The primary contribution of this research is its novel analysis and forecasting of health expenditure in the ASEAN region, which has been previously underexamined by scholars. Research Objectives: This research forecasts per capita health expenditure across three ASEAN countries, broken down by government, private, and out-of-pocket sources. Research Methods: This study employs a time series ARIMA model approach using secondary data from the World Bank for the period 2000 to 2021 Empirical Results: The findings indicate that projections for all three countries significantly increase across all health expenditure categories. Singapore is expected to see a sharp surge in all health expenditure components. At the same time, Indonesia is forecasted to achieve the highest growth rate in percentage terms, but lags in nominal terms. Conversely, Malaysia is projected to experience moderate growth in health expenditure. Implications: This research underscores the financing disparities and the urgent need for health system reform. JEL Classification: I18, C22, O53 How to Cite:Melati, A. P. S., & Sihaloho, E. D. (2025). The Future of Health Expenditure in ASEAN Countries: A Forecasting Analysis with ARIMA. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 449-466. https://doi.org/10.15408/sjie.v14i2.46420.